Kompetensi Digital dan Manajemen SDM TNI pada Era Revolusi Industri 4.0 - Prakosa, Chandra Ariyadi; Halkis, Mhd.; Susilo, Tarsisius (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
The main problem in managing TNI human resources in the Industrial Revolution 4.0 era is the skills gap in facing the demands of advanced technology. Many personnel are not fully ready to master technologies such as AI, big data, and IoT which are increasingly crucial in modern military operations. The purpose of this study is to analyze TNI Digital Competence and Human Resource Management in the Industrial Revolution 4.0 Era. The method used is qualitative descriptive using the SWOT approach. The results of the study show that digital transformation in human resource management and operations of the Indonesian National Army (TNI) in the Industrial Revolution 4.0 era is a crucial strategy to strengthen national defense. The use of technologies such as artificial intelligence (AI), big data, Internet of Things (IoT), and virtual simulation (VR) increases operational efficiency and the accuracy of TNI decision-making. This technology also facilitates more realistic and interactive personnel training and reduces the risks and costs of training. However, the success of this transformation is highly dependent on the readiness of infrastructure and budget. Cooperation with industry through public-private partnerships (PPP) is needed to accelerate infrastructure development such as 5G networks and cybersecurity systems. In addition, the development of competent human resources through continuous digital training is a key element in adapting to the dynamics of information-based global threats.